A review of quality procedures in the UK forensic sciences: What can the field of digital forensics learn?. Issue 1 (January 2019) - Page, Helen; Horsman, Graeme; Sarna, Anna; Foster, Julienne
Abstract: With a reliance on the various forms of forensic science evidence in complex criminal investigations, the measures for ensuring its quality are facing increasing scrutiny. Improvements to quality management systems, to ensure both the robust application of scientific principles and the accurate interpretation and reporting of results, have arisen as a consequence of high-profile rebuttals of forensic science evidence, combined with process improvements driven by evaluation of current practice. These improvements are crucial to ensure validity of results as well as providing assurance for all those involved in the Criminal Justice System. This work first examines the quality management systems utilised for the examination and analysis of fingerprint, body fluid and DNA evidence. It then proceeds to highlight an apparent lack of comparable quality assurance mechanisms within the field of digital forensics, one of the newest branches of forensic science. Proposals are provided for the improvement of quality assurance for the digital forensics arena, drawing on the experiences of, and more well-established practices within, other forensic disciplines. Highlights: A review of quality management procedures in the forensic sciences is offered. An assessment of the lack of quality management procedures in digital forensics. An analysis of peer-review strategies and methods for verifying work.